ADHERENCE TO THE ROUTINE NON-PHARMACOLOGIC INTERVENTIONS AMONG PATIENTS WITH CHRONIC ILLNESSES AT A RURAL HEALTH FACILITY SETTING OF UGANDA. A CROSS-SECTIONAL STUDY. - Irene Nakimera; David Serunjogi (Student's Journal of Health Research, 2023)
Background The study aimed at determining the prevalence of adherence to routine non-pharmacological interventions such as counseling, diet and regular physical exercises among patients in a rural health facility setting of Uganda. Methodology: A cross-sectional survey design was used to study 328 Patients who had spent at least 2 years with Chronic Illnesses such as Diabetes, HIV and hypertension accessing services at Luweero Health Centre IV. Simple random sampling technique was used to select the patients during visiting hours at the respective clinics from 20th of June 2018 to 20th of July 2018. The data was entered and analyzed using Statistical Package for Social Sciences (SPSS-Version 20). Results: A total of 326 patients with Chronic Illnesses were studied. 236 (72.4%) were having HIV, 54 (16.6%) were hypertensive, 25 (7.7%) were diabetic, and 11(3.4%) were having both HIV and hypertension. The prevalence of adherence to routine counseling is 69.6%, and this is highest among patients with hypertension (81.5%) and lowest among patients with Diabetes ( 56%). The prevalence of adherence to special diet is 71.5%, and is highest among patients with HIV and hypertension and those with HIV alone (91.1%) and lowest among patients with Hypertension (20.4%). The prevalence of adherence to routine physical exercises is 23.0%. This is highest among patients with Diabetes (48%) and lowest among patients with HIV (17.7%).   Conclusion: Majority (71.5%) of patients with chronic illnesses adhered to special diet, followed by counselling (69.6%) and only 23% of the patients adhered to physical exercises. Recommendation: The non-pharmacologic interventionists should design and institute group visiting mechanisms especially among patients that are unmarried if routine adherence is to be improved.